Spectrophotometric Estimation of Amoxycillin from Pharmaceutical Preparations - RAMI REDDY, N.; PRABHAVATHI, K.; CHAKRAVARTHY, I.E. (Asian Journal of Chemistry, 2010)
A new simple spectrophotometric method for determination of amoxycillin trihydrate was developed by bromination of the respective drug with brominating mixture in acidic medium. The excess brominating mixture is reacted with potassium iodide; astable yellow colour is developed. The absoibance of the yellow colour so- lution was measured at 350 nm on Spectronics-1001 spectrophotometer.